AKTIVITAS ENZIM PELARUT FOSFAT DAN EFEKTIVITAS MIKROBA ASAL WAMENA UNTUK MENUNJANG PERTANIAN RAMAH LINGKUNGAN PADA DAERAH MARGINAL - Widawati, Sri (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
The activity of phosphate solubilizing enzyme and the effectivity of microbe fromÃ‚Â Wamena for support agriculture of environmental friendliness at marginal area.Ã‚Â Phosphate dissolution of enzyme by microbial effective in compost plus from WamenaÃ‚Â forest was stored in the freezer for 4 years, have been conducted in EcofisiologyÃ‚Â laboratory,Microbiology devision, Research Center for Biology, Indonesian Institute ofÃ‚Â Science. This research was conducted to know the microbial affectivity and the activityÃ‚Â of phosphate solubilizing enzyme of 20 microorganisms in inoculants stored 4 years inÃ‚Â refrigerated room and to support soil fertility and biofertilizer agent in organic farmingÃ‚Â system. This research used plate count methode for counting the amount of microbialÃ‚Â population, Scinner method was used toanalizer enzyme of alkaline and acid PME-ase,and statistical analysis use Duncan methode. The storage of 20 inoculants invected 20microorganisms for 4 years in refrigerated room showed that the microbial activity stillÃ‚Â high with the amount of mean population 107 and the activity of phosphate solubilizingÃ‚Â enzyme with mean diameter of clear zone (holozone) 1 cm Ã¢â‚¬â€œ 2 cm. The effectivity and theÃ‚Â highest activity of phosphate solubilizing enzyme were : Azotobacter indicus (A), BacillusÃ‚Â panthothenticus (D), Bacillus megaterium (M), Bacillus thuringiensis (O), Ceratia sp. (R),Chromobacterium lividum (G), Chromobacterium violaceum (S), Flavobacterium breve(T), Klebsiella aerogenes (H), Pseudomonas fluorescent (J), Rhizobium legurxinosariumÃ‚Â (L), and the lowest were: Streptomyces sp. (I) .Key word: Alkaline and acid PMEase, Phosphate solubilizing bacteria,Biofertolizer